2012
DOI: 10.3346/jkms.2012.27.11.1371
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and Healthcare-Associated Risk Factors for Chronic Hepatitis C Virus Infection in Korea

Abstract: The risk factors related to hepatitis C virus (HCV) infection showed geographic and temporal differences. We investigated HCV-related risk factors in Korea where intravenous drug use (IVDU) is uncommon. The HCV-related risk factors were investigated in a prospective, multicenter chronic HCV cohort (n = 711) using a standardized questionnaire in four university hospitals. The results were compared with those of 206 patients with chronic liver diseases not related to either of HCV or hepatitis B virus infection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 33 publications
0
15
0
1
Order By: Relevance
“…In this study, 56·1% of patients positive for anti-HCV had detectable HCV RNA. Another study of 207 patients with chronic HCV infection 69 showed that risk factors for HCV infection include older age, needlestick injury, dental procedures, multiple sex partners (≥4), receiving a blood transfusion before 1991, and surgery.…”
Section: The Lancet Gastroenterology and Hepatology Commissionmentioning
confidence: 99%
“…In this study, 56·1% of patients positive for anti-HCV had detectable HCV RNA. Another study of 207 patients with chronic HCV infection 69 showed that risk factors for HCV infection include older age, needlestick injury, dental procedures, multiple sex partners (≥4), receiving a blood transfusion before 1991, and surgery.…”
Section: The Lancet Gastroenterology and Hepatology Commissionmentioning
confidence: 99%
“…Potential risk factors for HCV transmission in Korea includes blood transfusion before HCV screening, intravenous drug use, hemodialysis, needle stick injury, tattooing, dental procedures, and multiple sexual partners. 5 , 6 …”
Section: Discussionmentioning
confidence: 99%
“…The risk factors for HCV infection in South Korea includes transfusion before 1995, intravenous drug use, multiple sex partners, hemodialysis, needle stick injury, and tattooing. 5 , 6 Interestingly, even in the South Korea, there was significant difference in HCV prevalence among the geographic regions, showing characteristically high prevalence in southern coastal area of Jeonman, Gyeonman and Busan. 7 , 8 However, the cause of geographic difference of HCV prevalence in Korea is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Previous dental procedures and working abroad in neigbouring countries seem to play a role in this difference [14]. In a study related to healthcare associated risk factors for Chronic Hepatitis C infection in Korea it was observed that having multiple sex partners play a minor role in transmission [15]. In our study dental treatment, hospitalization, blood transfusion and history of operation were major risk factors in both regions but intravenous drug abuse were surprisingly a more important risk factor with a statistically significant difference in this eastern city of Turkey which prompted us to understand and explain the differences in terms of regions.…”
Section: Discussionmentioning
confidence: 99%